PHYTOCHEMICAL SCREENING OF BINAHONG LEAVES (Anredera cordifolia) FROM SEMARANG REGENCY EXTRACTED USING WATER SOLVENT - Anjani, Tiara Puspa; Hanifah, Hanifah (Jurusan Akuakultur, Universitas Bangka Belitung, 2022)
Binahong leaves (Anredera cordifolia) are a species from the Basellaceae family that has many benefits as an antibacterial, antitumor, wound healing, intestinal inflammation, and others. This is due to the presence of active ingredient compounds owned by Binahong leaves. This study aimed to screen for the active ingredient compounds present in Binahong leaf extract using water as a solvent. The method used in this study was fresh Binahong leaves mashed and then tested for active ingredient compounds including flavonoids, saponins, phenols, tannins, terpenoids, and steroids. The results obtained from this study were saponins and steroid compounds, while there were no flavonoids, terpenoids, tannins, or phenols.